Seroprevalence survey of brucellosis among rural people in Mongolia - Selenge Tsend; Zolzaya Baljinnyam; Bujinlkham Suuri; Enkhbayar Dashbal; Baatarkhuu Oidov; Felix Roth; Jakob Zinstag; Esther Schelling; Davaalkham Dambadarjaa (World Health Organization Regional Office for the Western Pacific, 2014)
Background: After the transition from socialism to a market economy in 1990, human brucellosis re-emerged in Mongolia. The aim of our study was to estimate a representative seroprevalence of Brucella spp. and to determine risk factors for brucellosis seropositivity among rural people. Methods: A cross-sectional study with multistage random selection was conducted in eight provinces of Mongolia. Study participants were interviewed using a questionnaire to obtain their brucellosis history, current symptoms and likely risk factors. Blood samples were drawn to determine brucellosis seroprevalence. Results: A total of 2856 randomly selected rural people aged four to 90 years were enrolled in the study. The seroprevalence of Brucella spp. was 11.1% (95% confidence interval [CI]: 10.0-12.1), ranging between 2.3% and 22.6% in the eight provinces; 39.2% (n = 609) of nomadic camps had at least one seropositive participant. Risk factors associated with brucellosis seropositivity were being older than 45 years (adjusted odds ratio [AOR] = 6.9, 95% CI = 5.1-8.7) and being a veterinarian (AOR = 2.8, 95% CI = 1.5-5.0). Conclusion: Our study confirms that human brucellosis seroprevalence among rural people in Mongolia is high. Human brucellosis can be effectively controlled if high-coverage livestock mass vaccination is implemented with a coverage survey after the vaccinations to ensure completeness. This mass vaccination should be accompanied by public awareness and educational programmes.